Cathepsin K: The Action in and Beyond Bone - Dai, Rongchen; Wu, Zeting; Chu, Hang Yin; Lu, Jun; Lyu, Aiping; Liu, Jin; Zhang, Ge (Frontiers in Cell and Developmental Biology, 2020)
Cathepsin K (CatK) is one of the most potent proteases in lysosomal cysteine proteases family, of which the main function is to mediate bone resorption. Currently, CatK is among the most attractive targets for anti-osteoporosis drug development. Although many pharmaceutical companies are working on the development of selective inhibitors for CatK, there is no FDA approved drug until now. Odanacatib (ODN) developed by Merck & Co. is the only CatK inhibitor candidate that demonstrated high therapeutic efficacy in patients with postmenopausal osteoporosis in Phase III clinical trials. Unexpectedly, due to the undesirable adverse effects in non-bone tissues, i.e. higher incidence of cardiovascular and cerebrovascular events versus the placebo group, the development of ODN was finally stopped. Therefore, it arouses widely interests for researchers to find out whether the activity of CatK has far-reaching effects throughout various organs besides bone tissues. Many studies have proved that CatK not only demonstrates vastly different functional activities beyond bone but also is involving in various diseases beyond the musculoskeletal system. This review summarizes the most essential functional roles of CatK in bone and beyond bone. Besides summarizing, we also highlight the potential off-target side effects of inhibiting CatK in non-bone areas in this review.